Quality Control Analysis of Product Defects Using Seven Tools Method & PDCA: Quality Control - Kenny Kenny; Handi Wilujeng Nugroho (Greeners: Journal of Green Engineering for Sustainability, 2026)
This study aims to analyze and control the quality of Tank Cold Water OPP model products using the Seven Tools method and the PDCA cycle. Production defect data from June 2023 to April 2024 (15 observation periods) were analyzed using checksheets, histograms, P-control charts, scatter diagrams, Pareto diagrams, and fishbone diagrams. Results show that out of 2,143,806 total production units, 79,995 defective units were recorded, yielding an average defect rate of 3.73%. Based on the Pareto diagram, Foreign Material is the most dominant defect type at 55.51%, followed by Blackdot (30.34%) and Oily (14.15%). Fishbone diagram analysis identified four main root-cause categories: machine, environment, method, and personnel. Corrective action proposals were formulated using the 5W+1H framework, covering periodic machine maintenance, production area housekeeping, SOP updates, and structured operator training. This research is expected to serve as a reference to pursuit of zero defect production.